The Influence of Product Quality, Brand Image, and Perceived Overclaim on Consumer Trust in The Originote Skincare Products - Alya Napsi Fitria; Dadan Abdul Aziz Mubarok (International Journal of Marketing & Human Resource Research, 2026)
This study aims to investigate how consumer perceptions of exaggerated claims, brand image, and product quality influence consumer trust in skin care products. Purposive sampling was used to select 100 respondents for this quantitative descriptive study. This study aims to investigate how consumer perceptions of exaggerated claims, brand image, and product quality influence consumer trust in skin care products (β = 0.435; t = 5.512; Sig. = 0.000). In addition, brand image has a significant and favorable impact (β = 0.548; t = 5.232; Sig. = 0.000). However, the perception of exaggerated claims has no significant impact (β = 0.024; t = 1.032; Sig. = 0.305). Consumer confidence is significantly influenced by these three factors together (F = 125.658; Sig. = 0.000). Based on an R2 of 0.797, product quality, brand image, and perceived exaggeration accounted for 79.7% of the variance in customer trust. Variables not included in the research model impacted the remaining 20.3%. The results showed that perceived exaggeration did not necessarily reduce customer trust. Product quality and brand image significantly impacted consumer trust. By showing that exaggerated product claims do not damage brand credibility and that quality and brand image remain strong, our findings reinforce the ethical marketing paradigm.